Navigated Pattern Laser System versus Single-Spot Laser System for Postoperative 360-Degree Laser Retinopexy. (14th December 2016) - Kulikov, Alexei N.; Maltsev, Dmitrii S.; Boiko, Ernest V.
Abstract : Purpose . To compare three 360°-laser retinopexy (LRP) approaches (using navigated pattern laser system, single-spot slit-lamp (SL) laser delivery, and single-spot indirect ophthalmoscope (IO) laser delivery) in regard to procedure duration, procedural pain score, technical difficulties, and the ability to achieve surgical goals. Material and Methods . Eighty-six rhegmatogenous retinal detachment patients (86 eyes) were included in this prospective randomized study. The mean procedural time, procedural pain score (using 4-point Verbal Rating Scale), number of laser burns, and achievement of the surgical goals were compared between three groups (pattern LRP (Navilas® laser system), 36 patients; SL-LRP, 28 patients; and IO-LRP, 22 patients). Results . In the pattern LRP group, the amount of time needed for LRP and pain level were statistically significantly lower, whereas the number of applied laser burns was higher compared to those in the SL-LRP group and in the IO-LRP group. In the pattern LRP, SL-LRP, and IO-LRP groups, surgical goals were fully achieved in 28 (77.8%), 17 (60.7%), and 13 patients (59.1%), respectively (p > 0.05 ). Conclusion . The navigated pattern approach allows improving the treatment time and pain in postoperative 360° LRP. Moreover, 360° pattern LRP is at least as effective in achieving the surgical goal as the conventional (slit-lamp or indirect ophthalmoscope) approaches with a single-spot laser.